ROLEPLAY: ONE ALTERNATIVE AND EFFETIVE TEACHING METHOD TO IMPROVE STUDENTS’ COMMUNICATION SKILL - Wienny Ardriyati (Dinamika Bahasa dan Budaya, 2009)
Most students study English and hope they can understand English actively. In fact, they don’t have a lot of chances to practice English in communication. They are reluctant to speak and afraid to make mistakes. They know much about English but they don’t know how to use it in communication. An effort to improve the students’ speaking skill is to use a role play as one method to teach English by creating English speaking atmosphere in class. In role play the students are set in a certain situation and they interact with their friends or partners to use English for communication. Key words: alternative, chances, atmosphere, role play